The congressionally directed medical research programs' Ovarian Cancer Academy: a new approach to training in biomedical research. Issue 1 (19th May 2022) - Wyatt, Tasha R.; Stepleman, Lara; Coleman, Taylor; Robinson, Leslie; Wylie, Karen; Levine, Douglas A.; Maihle, Nita J.
Abstract: Introduction: Researchers have begun to change their approach to training in the biomedical sciences through the development of communities of practice (CoPs). CoPs share knowledge across clinical and laboratory contexts to promote the progress of clinical and translational science. The Congressionally Directed Medical Research Programs' (CDMRP) Ovarian Cancer Academy (OCA) was designed as a virtual CoP to promote interactions among early career investigators (ECIs) and their mentors with the goal of eliminating ovarian cancer. Methods: A mixed-methods approach (surveys and interviews) was used to evaluate the effectiveness of the OCA for the eight ECIs and five mentors. Quantitative analysis included internal reliability of scales and descriptive statistics for each measure, as well as paired sample t -tests for Time 1 and Time 2. Qualitative data were analyzed for themes to discern which aspects of the program were useful and where more attention is needed. Results: Preliminary analyses reveal several trends, including the importance of training in grant writing to the ECI's productivity, as well as the value of peer mentorship. Conclusion: The results show that the OCA was an innovative and effective way to create a CoP with broad implications for the field of ovarian cancer research, as well as for the future of biomedical research training.